Building for the Future 2016 Annual Report - Floros, John D. (My University, 2016)
This informal report to the Kansas Legislature summarizes the wide-ranging impact of K-State Research and Extension in 2016, highlighting initiatives in agriculture, environmental stewardship, public health, and community development across Kansas.
UNN30_2016_01
Keywords: UNN30; Administrative and Research Reports; legislature